The Effect of Workload and Work Environment on Employee Performance at the Regional Secretariat of Seluma Regency - Komsatun Komsatun; Suswati Nasution; Nurzam Nurzam (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the effect of workload and work environment on employee performance at the Regional Secretariat of Seluma Regency. Samples in the study were 106 employees as Civil Servants at the Regional Secretariat of Seluma Regency. Collecting data using a questionnaire and the analytical method used is multiple linear regression, determination test and hypothesis testing. The results of the regression equation that is Y = 8.771- 0.332X1 + 0.470X2 + 3.085 means that the workload has a negative regression direction, if the workload increases then the performance will decrease. The work environment has a positive direction, meaning that if the work environment is better, the employee's performance will increase. The result of the determination test is 0.515 or (51.5%). This shows that the workload and work environment affect employee performance at the Regional Secretariat of Seluma Regency by 51.5%, while the rest (100 - 51.5% = 48.5%) are explained or influenced by other variables not examined. work and work environment together have an influence on employee performance at the Regional Secretariat of Seluma Regency with a significant value of 0.000 less than 0.05. Workload has a negative and significant effect on employee performance at the Regional Secretariat of Seluma Regency, because the significant value of 0.000 is smaller than 0.05. This illustrates that a high workload for employees at the Regional Secretariat of Seluma Regency will reduce employee performance. The work environment has a positive and significant impact on employee performance at the Regional Secretariat of Seluma Regency, with a significant value of 0.000, which is smaller than 0.05. This illustrates that a good work environment can improve employee performance.